1993
DOI: 10.3171/jns.1993.78.4.0661
|View full text |Cite
|
Sign up to set email alerts
|

Selective endovascular techniques in the treatment of cerebral mycotic aneurysms

Abstract: The aim of this study was to evaluate the role of endovascular treatment for intracranial mycotic aneurysms. The clinical and angiographic features of three patients with endocarditic vegetation (two with Streptococcus viridans and one with Staphylococcus) were reviewed retrospectively. Patients were selected for this treatment according to the clinical setting and aneurysm location. In two cases, selective catheterization of a distal middle cerebral and posterior cerebral artery branch with a microcatheter fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(26 citation statements)
references
References 9 publications
0
26
0
Order By: Relevance
“…6,11 This can be particularly useful in cases in which the aneurysm neck cannot be accessed by microcatheter and one is faced with sacrifice of the parent vessel, allowing avoidance of potentially devastating neurologic deficits.…”
Section: 24510mentioning
confidence: 99%
“…6,11 This can be particularly useful in cases in which the aneurysm neck cannot be accessed by microcatheter and one is faced with sacrifice of the parent vessel, allowing avoidance of potentially devastating neurologic deficits.…”
Section: 24510mentioning
confidence: 99%
“…Taken together, to achieve a satisfying prognosis, the types and locations of the aneurysms should be considered when performing the endovascular treatment for distal affected artery cavity using stents, reconstruction with stent in combination with coil embolization and coil embolization accompanied with occlusion of the parent artery (14,21,24). In both patients of our study, the arteries distal to the aneurysms were quite clear.…”
Section: Discussionmentioning
confidence: 99%
“…6,21,24,25,[29][30][31] The etiology of the AICA aneurysm is controversial: hemodynamic stress, embryonic vulnerability, flow-related vascular pathology, and arterial dissection by local trauma or nonspecific inflammation. 29,[32][33][34][35][36][37][38][39] Our study showed that 2 aneurysms were accompanied by AVMs and Moyamoya disease.…”
Section: Discussionmentioning
confidence: 99%